Pengembangan Panduan Teknik Sinema Edukasi untuk Meningkatkan Interaksi Sosial Siswa Sekolah Menengah Kejuruan - Muhamad Affan Rahmad Saputra; Henny Indreswari; Diniy Hidayatur Rahman; Muhamad Affan Rahmad Saputra; Henny Indreswari (Universitas Negeri Malang, 2022)
Abstract: This research and development aims to produce a guidance guide with educational cinema techniques to improve the social interactions of vocational students that meet the aspects of accuracy, usefulness, convenience, and attractiveness. This development research adapts the research developed by Borg and Gall which uses five stages, including: (1) Data collection (2) Planning (3) Product development (4) prototype validation stage (5) Product revision. The guide testing in stage four was carried out by two material experts, two media experts, and two potential users. The instrument used in this development research uses a material expert test acceptability rating scale, a media expert test acceptability rating scale, a prospective user test acceptability rating scale, to measure the acceptance of the prototype. The data obtained from this research are quantitative and qualitative data. Quantitative data analysis used the inter-rater agreement technique from Gregory. Qualitative data analysis was obtained from assessments carried out by experts and potential users in the form of input, criticism, and suggestions, then conclusions were drawn as a basis for improving the prototype. The results of quantitative data analysis from two material experts get an index of 1.00, two media experts get an index of 1.00, and two potential users get an index of 1.00 which means that they meet the aspects of accuracy, usability, convenience, and attractiveness. The results of qualitative data analysis from two material experts got five suggestions for improvement, two media experts got three suggestions for improvement, two potential users got two suggestions for improvement. Based on the results of the analysis, it can be concluded that the prototype developed has met the acceptability aspect so that the prototype of the guidebook is very suitable for use by counselors. Abstrak: Penelitian dan pengambangan ini bertujuan untuk menghasilkan sebuah panduan bimbingan dengan teknik sinema edukasi untuk meningkatkan interaksi sosial siswa SMK yang memenuhi aspek ketepatan, kegunaan, kemudahan, dan kemenarikan. Penelitian pengembangan ini mengadaptasi penelitian yang dikembangakan oleh Borg dan Gall yang menggunakan lima tahap, meliputi: (1) Pengumpulan data (2) Perencanaan (3) Pengembangan produk (4) tahap validasi prototipe (5) Revisi produk. Pengujian panduan pada tahap empat dilakukan oleh dua ahli materi, dua ahli media, dan dua calon pengguna. Instrumen yang digunakan dalam penelitian pengembangan ini menggunakan skala penilaian akseptabilitas uji ahli materi, skala penilaian akseptabilitas uji ahli media, skala penilaian akseptabilitas uji calon pengguna, untuk mengukur keberterimaan prototipe. Data yang diperoleh dari penelitian ini adalah data kuantitatif dan kualitatif. Analisis data kuantitatif menggunakan teknik inter-rater agreement dari Gregory. Analisis data kualitatif diperoleh dari penilaian yang dilakukan oleh ahli dan calon pengguna yang berupa masukan, kritik, dan saran, kemudian ditarik kesimpulan sebagai dasar dalam memperbaiki prototipe. Hasil analisis data kuantitatif dari dua ahli materi mendapatkan indeks 1,00, dua ahli media mendapatkan indeks 1,00, dan dua calon pengguna mendapatkan indeks 1,00 berarti memenuhi aspek ketepatan, kegunaan, kemudahan, dan kemenarikan. Hasil analisis data kualitatif dari dua ahli materi mendapatkan lima saran perbaikan, dua ahli media mendapatkan tiga saran perbaikan, dua calon pengguna mendapatkan dua saran perbaikan. Berdasarkan hasil analisis dapat disimpulkan prototipe yang dikembangkan telah memenuhi aspek keberterimaan sehingga prototipe buku panduan sangat layak digunakan oleh konsleor.